Single-pass transformation of syngas into ethanol with high selectivity by triple tandem catalysis - Jincan Kang (Nature Portfolio, 2020)
Direct synthesis of ethanol from non-petroleum carbon resources via syngas (CO/H2) is a highly attractive but challenging target. Here, the authors report a triple tandem catalytic system for single-pass conversion of syngas into ethanol with selectivity as high as 90%.